Cranial base flexion and skeletal jaw relationships in a sample of black South Africans - Nyakale, Mandla Dominic (University of Limpopo (Medunsa Campus), 2011)
Introduction: Flexion of the cranial base plays a very crucial role in the study of the craniofacial complex, particularly with the development of skeletal jaw relationships. An understanding of growth of the cranial base has come to assume great importance in orthodontics, and successful treatment of skeletal jaw malrelationships depends largely on the growth and flexion of the patients' cranial base. The aim of this study was to determine the relationship between cranial base flexion and skeletal jaw relationships in a sample of Black South Africans. Materials and method: The sample comprised of 300 pre-treatment lateral cephalograms of Black South Africans which was equally divided into Class I, Class . II and Class III skeletal jaw relationships according to the cephalometric tracing and analysis, and each class of skeletal jaw relationship had an equal number of male and female subjects. A digital cephalometric analysis software program (Orthview<ID, Netherlands) was used to trace and analyse the selected lateral cephalograms. The sample was first analysed to determine if gender differences existed for the mean cranial base flexion value in all three classes of skeletal jaw relationships. , , Comparisons among Class I, II and III mean cranial base flexton values using an independent t-test were made. The averag~ cranial base 'flexion value of the Black South Africans in this study was also compared with the average cranial base flexion value of Black and Caucasian South Africans from the previous studies for significance using an independent t-test. Results: Age distribution showed no statistically significant differences in all the three classes of skeletal jaw relationship (p > 0.05). There were no statistically significant differences between the mean cranial base flexion values of the male and female subjects in all the three classes of skeletal jaw relationships (p > 0.05). The results of this study demonstrated a significantly larger mean cranial base flexion value in the Class II skeletal jaw relationship sample when it was compared with the mean cranial base flexion values of Class I and Class III skeletal jaw relationship samples respectively (p < 0.05). There was no statistically significant difference between Class I and Class III skeletal jaw relationship samples with regards to the cranial base flexion (p> 0.05). The results of this study also showed no statistically . significant difference between the average cranial base flexion values of Black South Africans of the present study as well as Black and Caucasian South Africans of the previous study (p > 0.05). Conclusion: It was concluded that, in this sample, a larger cranial base flexion value is a feature of Class II skeletal jaw relationship and a smaller cranial base flexion value is a feature of both Class I and Class 11\ skeletal jaw relationships. Keywords: cranial base flexion, skeletal classification, skeletal jaw malrelationship
Thesis (M Dent (Orthodontics)) -- University of Limpopo, 2011
Keywords: Flexion; Skeletal jaw